2011
DOI: 10.1128/aem.03043-10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Copper Resistance Genes from Xanthomonas citri subsp. citri and Xanthomonas alfalfae subsp. citrumelonis

Abstract: Copper sprays have been widely used for control of endemic citrus canker caused by Xanthomonas citri subsp. citri in citrus-growing areas for more than 2 decades. Xanthomonas alfalfae subsp. citrumelonis populations were also exposed to frequent sprays of copper for several years as a protective measure against citrus bacterial spot (CBS) in Florida citrus nurseries. Long-term use of these bactericides has led to the development of copperresistant (Cu r ) strains in both X. citri subsp. citri and X. alfalfae s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
172
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 39 publications
2
172
0
Order By: Relevance
“…actinidiae in New Zealand (2). Continual use of copper can lead to a toxic buildup of copper residues within the environment (27,28), and bacterial resistance to copper has been documented (29)(30)(31)). …”
mentioning
confidence: 99%
“…actinidiae in New Zealand (2). Continual use of copper can lead to a toxic buildup of copper residues within the environment (27,28), and bacterial resistance to copper has been documented (29)(30)(31)). …”
mentioning
confidence: 99%
“…The copABCD genes, which were first described in a plasmid of P. syringae pv. tomato PT23 (8), is an important determinant of copper resistance in P. syringae and other phytopathogenic bacteria (6,8,9,(12)(13)(14). However, additional studies have shown that P. syringae may harbor other variants of Cu r determinants (3, 7, 15).…”
mentioning
confidence: 99%
“…Under these conditions, frequent sprays of copper‐based bactericides are required, increasing production costs as well as environmental contamination, without necessarily providing adequate protection. Moreover, frequent sprays with relatively high concentrations of Cu might cause phytotoxicity and often lead to emergence of Cu‐resistant strains (Hancock, 2001; Behlau et al ., 2011; Worthington et al ., 2012). Therefore, there is an urgent need to develop novel technologies to manage and prevent bacterial plant diseases and prevent food loss.…”
Section: Introductionmentioning
confidence: 99%